Measurement and prediction of residual strains and stresses during the cooling of a glass fibre reinforced PA66 matrix composite. (October 2020) - Péron, Mael; Jacquemin, Frédéric; Casari, Pascal; Orange, Gilles; Bikard, Jérôme; Bailleul, Jean-Luc; Boyard, Nicolas
Abstract: The forming process of thermoplastic composites inevitably leads to the development of residual stresses. This study proposes a model to predict the residual stresses at the ply scale of a thermoplastic composite laminate. It accounts for the heat transfer, crystallization kinetics and mechanical behaviour of the laminate. The model is applied to the cooling of a polyamide 66 (PA66) matrix reinforced with continuous glass fibres. The Stress Free Temperature is considered as the starting point of stresses accumulation within each ply and its identification is discussed. The curvatures of [904 /04 ] laminates and their evolution with temperature are recorded with a digital image correlation technique. They are compared to the curvatures predicted by the model, which permits to validate it. The predicted stresses distribution is then discussed. Finally, the model is compared to the Classical Lamination Theory, demonstrating the interest of the developed model.